2021
DOI: 10.1055/a-1293-7746
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided transgastric drainage of radiologically inaccessible left lobe liver abscess involving segment 4, caudate lobe, and left lateral segments using a modified technique

Abstract: Liver abscess requiring drainage is conventionally managed by interventional radiology-guided percutaneous drainage (PCD). Radiologically inaccessible abscesses are managed with laparoscopic or open surgery, which carries high rates of morbidity and mortality.EUS-guided transluminal liver abscess drainage is minimally invasive and can be an alternative approach for caudate lobe, segment 4, and left lateral segment abscesses. We report on three consecutive patients with radiologically inaccessible left lobe liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, ethanol injection therapy is not recommended for liver cysts with biliary communication. [ 9 , 16 , 34 ] In our case, sclerotherapy using minocycline was ineffective. Therefore, EUS-guided ethanol injection was not performed.…”
Section: Discussionmentioning
confidence: 59%
“…However, ethanol injection therapy is not recommended for liver cysts with biliary communication. [ 9 , 16 , 34 ] In our case, sclerotherapy using minocycline was ineffective. Therefore, EUS-guided ethanol injection was not performed.…”
Section: Discussionmentioning
confidence: 59%
“…Table 2 depicts the details of the included studies with type of stent, indication of EUS-guided drainage, size of caudate lobe abscess, etiology of abscess and complications of EUS-guided drainage. 4,[7][8][9][10][11][12][13][14][15] The details of excluded studies with reason of exclusion are shown in Supplementary Table 2, Supplemental Digital Content 1, http://links.lww.com/SLE/A407. 3,[16][17][18][19] Ten studies reported outcomes of EUS-guided drainage of caudate lobe abscess in 17 patients.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Most are drained percutaneously, although 14 case reports and three retrospective studies have been published regarding EUS-guided drainage (Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In these previous reports, the most common indication for EUS-guided liver abscess drainage was failed medical therapy and inability to drain the abscess percutaneously. Seewald et al 4 first described EUS-guided liver abscess drainage in 2005, reporting that the entire left lobe and most of the central segments of the liver were well visualized and accessible using this technique.…”
Section: Eus-guided Liver Abscess Drainagementioning
confidence: 99%